Navigacijski sistemi v skeletni kirurgiji - Štivan, Feri (Zdravniški vestnik, 2005)
Background. Surgical navigation system are incresingly being used during trauma and orthopaedic surgery. The conceptual design of each of these devicesis similar. The authors define three major components involved in the clinical aplication of surgical navigation: a surgical object, a virtual object and a navigator. These three elements are connected by registration andreferencing. There are many pitfalls in aplication of CAOS. Many applications will be presented and their advantages and disadvantages will be elucidated. Conclusions. More and more studies prove the superiority of the CAOS approaches over classic techniques in a number of applications. It is essential to know the basics and the limitations of the underlying technical principles. There is a considerable chance for using these devices incorrectly. From an economical point of view only the optimal performance of a navigation system will probably justify its significant investment costs.
Keywords: Hrbtenica; kirurgija; kirurško zdravljenje; Medenične kosti; navigacijski sistemi; Pelvic Bones; Robotics; Robotika; Spine; Surgery; Traumatology; Travmatologija